Interests of Students in Geoscientific Topics: Results of a Study of Interests Within the Context of the Project "Forschungsdialog System Erde" - Hemmer, Ingrid; Hemmer, Michael; Bayrhuber, Horst; Häußler, Peter; Hlawatsch, Sylke; Hoffmann, Lore; Raffelsiefer, Marion (Journal of Geography Education, 2005)
The study, embedded in the interdisciplinary project "Forschungsdialog System Erde" ("research dialogue system of the earth"), which was carried out at the IPN in Kiel, generally shows a medium interest in geoscientific fields of subject with school boys and girls. The most interesting topics are those, that are related to human beings and to life/living beings or environmental threat, respectively, such as "earthquakes" or "climatic changes". The interest in a topic correlates with the context that it is related to. Young adults share a relatively high interest in the topics "individual", "society" as well as "social responsibility". Concerning special learning techniques and methods of working in class there is a particular tendency towards action-oriented working methods like the carrying out of geoscientific experiments. The results can be used in class by combining topics, which are unpopular with students, with a preferred context and a popuiar method of working, respectively. In their spare time youths seldom occupy with geoscientific subjects. This underlines the important role of school lessons in raising the student’s interest in these fields. In school geography covers geoscientific contents far more than biology, while chemistry and physics insufficiently deal with geoscientific phenomenon. Therefore it is rightly to claim that the subject geography is the centring geoscientific subject This is why it is necessary to call the subject geography the centring geoscientific subject in school.